2005
DOI: 10.1159/000082523
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic Efficacy of an Oral Suspension of Granisetron plus Dexamethasone and Influence of Quality of Life on Risk for Nausea and Vomiting

Abstract: Objectives: To assess the antiemetic efficacy of an oral suspension of granisetron/dexamethasone in patients receiving chemotherapy and to determine whether quality-of-life parameters influence the risk for postchemotherapy nausea and vomiting (PCNV). Patients and Methods: In an open monocentric study, an oral suspension containing 2 mg granisetron and 16 mg (4 mg for moderately emetogenic chemotherapy) dexamethasone was administered to 43 chemotherapy-naive patients before highly (n = 16) or moderately (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Along with the intervention group, the control group was simultaneously receiving professional advice from doctors on countermeasures, routine follow-up in the hospital, and gradual recovery of lesions deriving from disease and treatment. 9 In patients with stage 2 tumors, the survival rate in the intervention group was 94.74% (108/114), whereas it was 80.67% in the control group (P < .01). There is thus a striking difference between groups, which indicates that the complex healing intervention affects survival rate in this stage.…”
Section: Effects Of Intervention On 2-year Survival By Tumor Stagementioning
confidence: 89%
“…Along with the intervention group, the control group was simultaneously receiving professional advice from doctors on countermeasures, routine follow-up in the hospital, and gradual recovery of lesions deriving from disease and treatment. 9 In patients with stage 2 tumors, the survival rate in the intervention group was 94.74% (108/114), whereas it was 80.67% in the control group (P < .01). There is thus a striking difference between groups, which indicates that the complex healing intervention affects survival rate in this stage.…”
Section: Effects Of Intervention On 2-year Survival By Tumor Stagementioning
confidence: 89%
“…According to available literature, the usual rate of emesis control in chemotherapy with moderate or high emetic potential using 5-HT 3 receptor antagonists is between 40% and 86%. [59][60][61][62][63][64] The higher rates of emesis control in moderately emetogenic chemotherapy are achieved with 2-drug regimens combining 5-HT 3 antagonists and dexamethasone (75% in acute emesis and 92% in delayed emesis). 6,59,60 In highly emetogenic chemotherapy, the higher rates of emesis control are achieved with 3-drug regimens combining 5-HT 3 antagonists, dexamethasone, and aprepitant (83% to 93% in acute emesis and 79% to 76% in delayed emesis).…”
Section: Discussionmentioning
confidence: 99%
“…6,27,28,64,[68][69][70] The clinical trials that included specifically granisetron combined with dexamethasone reported a rate of complete emesis control in 60% and 86% of patients, higher than the 70% with intravenous granisetron, 61 and 60% to 86% with oral granisetron. [62][63][64] A recent phase III clinical trial comparing palonosetron plus dexamethasone with intravenous granisetron plus dexamethasone in highly emetogenic chemotherapy reported a 73.3% complete response with granisetron plus dexamethasone. 42 It is not possible compare these findings (2-or 3-drug regimens) with the results of transdermal granisetron trials, because only granisetron monotherapy was used.…”
Section: Discussionmentioning
confidence: 99%
“…In highly emetogenic chemotherapy, the higher rates of emesis control are achieved with 3-drug regimens combining 5-HT 3 antagonists, dexamethasone, and aprepitant (83% to 93% in acute emesis and 79% to 76% in delayed emesis) 6,27,28,64,6870. The clinical trials that included specifically granisetron combined with dexamethasone reported a rate of complete emesis control in 60% and 86% of patients, higher than the 70% with intravenous granisetron,61 and 60% to 86% with oral granisetron 6264. A recent phase III clinical trial comparing palonosetron plus dexamethasone with intravenous granisetron plus dexamethasone in highly emetogenic chemotherapy reported a 73.3% complete response with granisetron plus dexamethasone 42…”
Section: Discussionmentioning
confidence: 99%